Legal Protection of Personal Data in Relation to The Use of Cloud Computing in Indonesia - Gomulia Oscar; Nurmawati Nurmawati; Adi Darmawansyah (Riviera Publishing, 2025)
Rapid developments in information technology have encouraged the use of cloud computing as a solution for data storage and processing, including personal data. However, despite its benefits, cloud computing systems carry serious risks of data leaks and misuse. This study aims to examine legal protection regulations for personal data in the context of cloud computing use in Indonesia and analyze the legal challenges in implementing personal data protection in cloud computing services in Indonesia. The research uses a normative juridical method with a regulatory approach and other secondary legal materials. The results show that Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) provides a comprehensive legal basis for personal data protection, including in the context of cloud computing. The PDP Law regulates the rights of data subjects, the obligations of data controllers and processors, and provisions for cross-border data transfers. However, the implementation of this law faces various challenges, such as delays in establishing a supervisory authority, the absence of implementing regulations, low digital legal literacy, and the unpreparedness of business actors, especially cloud-based service providers. To ensure the effectiveness of personal data protection in the era of cloud computing, further steps are needed, such as the establishment of an independent supervisory authority, the enactment of implementing regulations, the improvement of digital legal literacy, and the strengthening of international cooperation. The legal challenges in the implementation of personal data protection in cloud computing services in Indonesia stem from the lack of readiness of derivative regulations, the non-functioning of the supervisory authority, and the weak legal infrastructure and awareness of business actors. To overcome this, systematic steps are needed, including accelerating the establishment of a supervisory agency, drafting detailed implementing regulations, and increasing legal literacy and compliance by all stakeholders.